Surgical instrumentation: from undergraduate education to required competences in hierarchical positions in the autonomous city of buenos aires, argentina - Moauro, Yasmín Dana; Scafat, Iael; Franco, Juan Víctor Ariel; Esteban, Santiago (Revista del Hospital Italiano de Buenos Aires, 2019)
The incorporation of a bachelor’s degree for surgical-instrumentation practitioners, the academic field aims to develop the competencies required by professionals in management positions while improving the ones of surgical-instrumentation practitioners in an operating room. The following research articulated the academic training provided by different higher education institutions with the competences required to perform in several hierarchical positions. We conducted a qualitative, descriptive and cross-sectional study: we carried out interviews with seven health-professionals who work in different hierarchical roles, using open-ended questions, whose answers were studied through content analysis; and we analyzed the study-plans for Surgical Instrumentation degrees offered by a select group of universities. We also compared the lists of the subjects of the different universities that are offered in the degree for surgical instrumenters, collating the results with the interviews. The interviews revealed that graduates often get middle-level management roles that require not only the competences directly related to their surgical-assistance practice, but also a set of skills regarding human-management, such as administration, communication and leadership among others. Generally, in the analyzed bachelor’s degrees curricula, the contents are properly organized and provide students with abilities in management, administration, investigation and education, concluding undergraduate academic education is an added value in graduates’ resume for labor insertion. However, it exits a variation in the subject’s content between higher education institutions, which creates a disparity in the academic level between graduates from different universities and force some of them to take further courses and trainings to complement their academic background